Cinnamophilin overcomes cancer multi-drug resistance via allosterically modulating human P-glycoprotein on both drug binding sites and ATPase binding sites - Yu-Ning Teng (Elsevier, 2021)
Cancer multi-drug resistance (MDR) caused by P-glycoprotein (P-gp) efflux is a critical unresolved clinical concern. The present study analyzed the effect of cinnamophilin on P-gp inhibition and MDR reversion. The effect of cinnamophilin on P-gp was investigated through drug efflux assay, ATPase assay, MDR1 shift assay, and molecular docking. The cancer MDR-reversing ability and mechanisms were analyzed through cytotoxicity and combination index (CI), cell cycle, and apoptosis experiments. P-gp efflux function was significantly inhibited by cinnamophilin without influencing the drug’s expression or conformation. Cinnamophilin uncompetitively inhibited the efflux of doxorubicin and rhodamine 123 and exhibited a distinct binding behavior compared with verapamil, the P-gp standard inhibitor. The half maximal inhibitory concentration of cinnamophilin for doxorubicin and rhodamine 123 efflux was 12.47 and 11.59 μM, respectively. In regard to P-gp energy consumption, verapamil-stimulated ATPase activity was further enhanced by cinnamophilin at concentrations of 0.1, 1, 10, and 20 μM. In terms of MDR reversion, cinnamophilin demonstrated synergistic cytotoxic effects when combined with docetaxel, vincristine, or paclitaxel. The CI was < 0.7 in all experimental combination treatments. The present study showed that cinnamophilin possesses P-gp-modulating effects and cancer MDR resensitizing ability.